Disease progression model in subjects with mild cognitive impairment from the Alzheimer's disease neuroimaging initiative: CSF biomarkers predict population subtypes. (14th December 2012) - Samtani, Mahesh N.; Raghavan, Nandini; Shi, Yingqi; Novak, Gerald; Farnum, Michael; Lobanov, Victor; Schultz, Tim; Yang, Eric; DiBernardo, Allitia; Narayan, Vaibhav A.; ,
<x xml:space="preserve">Abstract</x> WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT Amnestic mild cognitive impairment MCI) represents the prodromal stage of Alzheimer's dementia and this disease progresses in a non‐linear fashion. Disease progression depends on a variety of demographic, biochemical, genetic and cognitive factors. WHAT THIS STUDY ADDS Baseline CSF biomarkers carry information about disease pathology and critical thresholds for these markers (Aβ and p‐tau181P) have been identified that allow segregation of the population into MCI progressers and non‐progressers. AIM The objective is to develop a semi‐mechanistic disease progression model for mild cognitive impairment (MCI) subjects. The model aims to describe the longitudinal progression of ADAS‐cog scores from the Alzheimer's disease neuroimaging initiative trial that had data from 198 MCI subjects with cerebrospinal fluid (CSF) information who were followed for 3 years. METHOD Various covariates were tested on disease progression parameters and these variables fell into six categories: imaging volumetrics, biochemical, genetic, demographic, cognitive tests and CSF biomarkers. RESULTS CSF biomarkers were associated with both baseline disease score and disease progression rate in subjects with MCI. Baseline disease score was also correlated with atrophy measured using hippocampal volume. Progression rate was also predicted by executive functioning as measured by the Trail B‐test. CONCLUSION CSF biomarkers have the ability to discriminate MCI subjects into sub‐populations that exhibit markedly different rates of disease progression on the ADAS‐cog scale. These biomarkers can therefore be utilized for designing clinical trials enriched with subjects that carry the underlying disease pathology.